The unequal distribution of credit: Is there a role for monetary policy? - Samuel Ligonnière; Salima Ouerk (National Bank of Belgium, 2025)
We analyze the dynamic effects of ECB monetary policy surprises on newly originated mortgage credit across the household income distribution using loan-level data from the French national credit registry. We find a distinct U-shaped pattern in mortgage borrowing across income groups, with loans for primary residences taken by middle-income households showing the strongest reaction. These households, while creditworthy, have liquidity constraints which make them more sensitive to changes in financing conditions and macroeconomic signals than other groups. Our analysis of transmission channels confirms these findings. Credit demand reacts positively to expansionary pure monetary policy and forward guidance surprises, underscoring the central role of the expectations channel. In quantitative terms, we estimate that a one-standard deviation expansionary surprise over two years leads to a 10% increase in new mortgage lending for primary residences among middle-income households. In addition, credit demand increases in response to positive macroeconomic signals, pointing to the role of the information channel.
Keywords: D31; E4; E52; G21; G5; G51; 330; monetary policy; credit distribution; inequality